Analisis Faktor-Faktor yang Mempengaruhi Kepatuhan Perawat dalam Melaksanakan Standar Asuhan Keperawatan - Asmadi, Andi; Menap, Menap (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
This study aims to identify the factors influencing nurse compliance in implementing nursing care procedures at RSUD Praya Lombok Tengah, focusing on the surgical, internal medicine, and pediatric wards. This observational analytic study uses a cross-sectional design involving 36 nurses as respondents. The variables analyzed include education, salary, rewards, work interaction, and safety. The research instruments used include questionnaires, interviews, and checklists. The questionnaire was used to measure respondents' demographics, salary, rewards, work interaction, and safety, while compliance was measured using a checklist. Data analysis using chi-square and regression tests showed that none of the independent variables had a significant influence on nurse compliance. The logistic regression test results showed significance values for income (Sig. = 0,487), work interaction (Sig. = 0,721), rewards (Sig. = 0,516), and safety (Sig. = 0,571), all of which were greater than 0.05, indicating no significant influence. However, it can be concluded that a holistic approach still plays an important role in improving nurse compliance.